'As though Miles of Ocean did not Separate us': Print and the Construction of a Transatlantic Free Love Community at the Fin de Siècle. (29th November 2019) - Jones, Sarah L
Abstract: This article argues that British and American free lovers – radical sexual reformers committed to the cause of 'sexual freedom' – came together through print to build a transatlantic community at the fin de siècle. Challenging existing narratives that characterize free love as isolated or incoherent, it argues that through print free lovers from Britain and America were able to forge links with each other, and to construct an important, coherent collective identity that transcended national boundaries. In doing so it makes two major interventions. First, it provides unique new insights into the history of free love in both the British and American contexts, placing a new focus on often overlooked transnational connections and exchanges that helped to shape late nineteenth-century free love campaigns. Second, it encourages historians to rethink the ways we look for and make sense of cohesive international reform communities more broadly in this period. By exploring how a small, radical group like the free lovers were able to cohere through processes of contestation and negotiation played out entirely in print, this article will show that, where necessary, print was enough for transatlantic reformers to construct common identities and negotiate coherent reform ideas. As such, it argues that historians of fin-de-siècle social reform should look again at the print culture of other contemporary reformers otherwise labelled divided, isolated, or marginalized to look for threads of cohesion, cooperation, and compromise.